Investigação dos efeitos antimicrobiano, citotóxico e genotóxico do óleo essencial das partes aéreas de Croton tricolor Klotsch ex Baill (Euphorbiaceae) - Ferreira, Sávio Benvindo (2014)
The use of plant products for the treatment, prevention and cure of diseases , is one of the oldest forms of medical practice of humanity , and although great advances observed in modern medicine are natural products still contribute considerably in care health . Among the therapeutic actions of medicinal plants, antimicrobial activity is one of the most important front of the existing rate of mortality and antimicrobial resistance. Although plants possess many therapeutic uses that are traditionally known, the human being unaware of the fact that they can be toxic both for humans and for animals. Croton tricolor ex Klotsch Baill, popularly known as silvery quince is native caatinga of Northeast Brazil. Thus, the present study aimed to investigate the biological effects of essential oil from leaves of Croton tricolor Klotsch ex Baill (Ct-OE). The minimum inhibitory concentration (MIC) for Staphylococcus aureus ATCC 25925 was 6.7 mg/ml, Staphylococcus aureus ATCC 25619 3.35 mg/ml Staphylococcus aureus ATCC 8539 was 1.68 mg/mL and E. coli ATCC 25922 was 3.35 mg/mL. For E. coli strains of clinical origin MIC ranged from 1.67 to 3.35 mg/ml. In cytotoxicity against human erythrocytes, the essential oil exhibited a low level of hemolysis in blood A + and B +, but caused in type O + erythrocytes. The Ct -OE showed a slight increase in oxidation in erythrocytes, but a value much lower than phenylhydrazine (Ph). However, the Ct-OE could protect erythrocytes from oxidation by Ph more efficiently than vitamin C. The Ct -OE did not cause structural chromosomal damage and/or number of erythrocytes in mice in vivo.